Udiebot: Implementasi Inverse Kinematic pada Quadruped Robot - Nuril Esti Khomariah; Samsul Huda (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2018)
Quadruped robot is a multi-legged robot driven by 4 legs. During this time, the way to move a robot's leg is to give a direct value for each joint. This certainly requires a longer time because it still uses the trial-error method and if the joint owned by the robot is very much. Therefore this problem can be overcome by using the inverse kinematic. Inverse kinematic can accelerate the process of defining foot poses with coordinate as input and values for each joint / robot joint as output. At Udiebot, each leg has 3 DOF (degree of freedom) with a total 12 DOF. Robot foot mechanical parameters need to be defined first including the forward kinematic model. Then proceed with inverse kinematic implementation which is analyzed by geometry approach. From the test results it can be seen that the maximum error obtained is around 0.11% which indicates that the system is running well. Keywords: Quadruped robot, inverse kinematic, pose, forward kinemat